Optimizing Layout for Material Handling Cost Reduction Using Blocplan and FlexSim: A Case Study in Screen Printing Production - Khofiyah, Nida An; Azizurrohman, Abdul; Suhendra, Suhendra; Prasetya, Dwi Indra; Mukhlisin, Mukhlisin (Politeknik Negeri Batam, 2025)
Small-scale screen printing businesses often face challenges related to limited production space and high material handling costs, which reduce production efficiency. This research aims to design an efficient facility layout and reduce material handling costs at Usaha Sablon XYZ by using the Systematic Layout Planning (SLP) method combined with the BLOCPLAN algorithm and FlexSim. The methodology involves direct observation, interviews, initial layout measurements, and analysis using tools such as Activity Relationship Chart (ARC), Form to Chart (FTC), and Operation Process Chart (OPC). The proposed layouts produce two alternatives, with Layout Proposal 2 showing the best efficiency, reducing total material handling cost from Rp 11.999.965 to Rp 7.734.185,65 a cost reduction of 35.55%. The results indicate that BLOCPLAN and Flexsim was effective within the context of this case study in generating layout alternatives that reduce material handling cost.